Determinants of adoption of improved panicum forage by agro- pastorals in Dasenech District, Southern Ethiopia - Adala, Asmera; Alemayehu, Yidnekachew; Darcho, Dawit (Journal of Agriculture and Environmental Sciences, 2022)
Adoption of improved forage remains vital in combating feed shortages and reducing livestock deaths in pastoral and agro-pastoral areas of Ethiopia. However, it depends on household characteristics, institutional and socioeconomic factors, and the perception of the community. Thus, this study examined the determinants of adoption and intensity of improved panicum forage technologies in the Dasenech district. A multistage sampling technique was employed to select 140 forage-producing agro-pastoral households. A double hurdle model was used to analyze the data. The results indicated that agro-pastoralists’ adoption and intensity of adoption of panicum forage production in the Dasenech district is high. However, more than 60% of agro-pastoralists who had adopted and cultivated panicum forage claimed problems in accessing irrigation water, which was associated with high fuel for operating irrigation water pumps. Moreover, the probability of adoption of panicum forage production in the district is influenced by access to irrigation water, forage production experience, cooperative membership, and distance to the training center. The intensity of adoption of panicum forage production was also influenced by the sex of the respondent, credit access, distance to market, production experience, price of seed, and livestock holdings. Working on issues related to the improvement of access to irrigation water, establishing cooperatives of agro-pastoralists, and provision of credit opportunities and market information by respective stakeholders is proposed to enhance the adoption and production of panicum forage in the study area.